A proposed data set for analyzing the labor market trajectories of East Germans around reunification - Hannah Liepmann; Dana Müller (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Data from German social security notifications and internal procedures of the Federal Employment Agency are an important source for analyzing labor market trajectories. However, for East Germans these data are only fully available from 1992 onwards. As a consequence of German reunification, by 1992 significant fractions of East Germans had already lost their jobs, had changed their occupations and industries, and had moved to West Germany. We partially close the gap in the data by linking the "Integrated Employment Biographies" - that start in 1992 for East Germany - with the GDR's "Data Fund of Societal Work Power" from 1989. The new data set permits the analysis of phenomena such as unemployment, job mobility, and regional mobility. It can also be used to refine the existing knowledge of the individual-level labor market consequences of German reunification. Our long-term goal is to make the new data set available to the research community via the Research Data Center of the Federal Employment Agency. @Die Daten aus der deutschen Sozialversicherung und den internen Prozessen der Bundesagentur für Arbeit sind eine wichtige Quelle für die Analyse von Arbeitsmarktbiographien. Für Ostdeutsche sind diese Daten allerdings erst ab 1992 vollständig verfügbar. Als Folge der deutschen Wiedervereinigung hatten bis 1992 bereits große Anteile von Ostdeutschen ihre Arbeit verloren, ihre Berufe und Industriezweige gewechselt und waren nach Westdeutschland umgezogen. Wir schließen die Lücke in den Daten teilweise, indem wir die "Integrierten Erwerbsbiographien" - welche 1992 für Ostdeutschland beginnen - mit dem 'Datenspeicher Gesellschaftliches Arbeitsvermögen' der DDR aus dem Jahr 1989 verknüpfen. Der neue Datensatz ermöglicht die Analyse von Phänomenen wie Arbeitslosigkeit, berufliche Mobilität und regionale Mobilität. Er kann außerdem genutzt werden, um das bestehende Wissen über die Konsequenzen der deutschen Wiedervereinigung für individuelle Arbeitsmarktbiographien zu verfeinern. Unser langfristiges Ziel ist es, den neuen Datensatz für die Forschungsgemeinschaft über das Forschungsdatenzentrum der Bundesagentur für Arbeit verfügbar zu machen.
Keywords: 330; East Germany; German reunification; labor market trajectories; administrative data; record linkage